2017
DOI: 10.1051/matecconf/201712402003
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Tolling for Mixed Urban Freight and Passenger Traffic

Abstract: Abstract. This paper investigates the welfare effects of optimal tolling on urban traffic congestion, in a bottleneck model, with mixed freight and passenger users. T he users' marginal utility of time is considered to be varying with time. Under both no-toll equilibrium and socially optimal tolling, the users are found to sort their arrival time according to the increasing rates of marginal utility at the destination. The optimal toll that maximizes social we lfare does not change each user's indirect utilit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The study also calculated an optimal value of congestion charge, which was around USD 0.18 [23]. In a similar study in the context of passenger and freight vehicles, it was concluded that the revenue generated from congestion pricing can be redistributed among the users of this policy as an incentive, which can lead to enhancing social welfare [24].…”
Section: Pricing and Reward Strategiesmentioning
confidence: 89%
“…The study also calculated an optimal value of congestion charge, which was around USD 0.18 [23]. In a similar study in the context of passenger and freight vehicles, it was concluded that the revenue generated from congestion pricing can be redistributed among the users of this policy as an incentive, which can lead to enhancing social welfare [24].…”
Section: Pricing and Reward Strategiesmentioning
confidence: 89%
“…In China, where the rate of urbanisation soared during the past decade, road pricing research was given priority in recent times as a strategy to decrease congestion and roadbased emissions [49,50]. Studies undertaken in China explored public acceptance and legislation [51]; time varying on-street parking pricing revenue [52]; and optimal road pricing charges [53].…”
Section: Geographical Distribution Of Research Activitymentioning
confidence: 99%